Detection of IMP-4 and SFO-1 co-producing ST51 Enterobacter hormaechei clinical isolates - Qiao, Jie; Ge, Haoyu; Xu, Hao; Guo, Xiaobing; Liu, Ruishan; Li, Chenyu; Chen, Ruyan; Zheng, Beiwen; Gou, Jianjun (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose To explore the genetic characteristics of the IMP-4 and SFO-1 co-producing multidrug-resistant (MDR) clinical isolates, Enterobacter hormaechei YQ13422hy and YQ13530hy. Methods MALDI-TOF MS was used for species identification. Antibiotic resistance genes (ARGs) were tested by PCR and Sanger sequencing analysis. In addition to agar dilution, broth microdilution was used for antimicrobial susceptibility testing (AST). Whole-genome sequencing (WGS) analysis was conducted using the Illumina NovaSeq 6000 and Oxford Nanopore platforms. Annotation was performed by RAST on the genome. The phylogenetic tree was achieved using kSNP3.0. Plasmid characterization was conducted using S1-pulsed-field gel electrophoresis (S1-PFGE), Southern blotting, conjugation experiments, and whole genome sequencing (WGS). An in-depth study of the conjugation module was conducted using the OriTFinder website. The genetic context of blaIMP-4 and blaSFO-1 was analyzed using BLAST Ring Image Generator (BRIG) and Easyfig 2.3. Results YQ13422hy and YQ13530hy, two MDR strains of ST51 E. hormaechei harboring blaIMP-4 and blaSFO-1, were identified. They were only sensitive to meropenem, amikacin and polymyxin B, and were resistant to cephalosporins, aztreonam, piperacillin/tazobactam and aminoglycosides, intermediate to imipenem. The genetic context surrounding blaIMP-4 was 5′CS-hin-1-IS26-IntI1-blaIMP-4-IS6100-ecoRII. The integron of blaIMP-4 is In823, which is the array of gene cassettes of 5′CS-blaIMP-4. Phylogenetic analysis demonstrated that E. hormaechei YQ13422hy and YQ13530hy belonged to the same small clusters with a high degree of homology. Conclusion This observation revealed the dissemination of the blaIMP-4 gene in E. hormaechei in China. We found that blaIMP-4 and blaSFO-1 co-exist in MDR clinical E. hormaechei isolates. This work showed a transferable IncN-type plasmid carrying the blaIMP-4 resistance gene in E. hormaechei. We examined the potential resistance mechanisms of pYQ13422-IMP-4 and pYQ13422-SFO-1, along with their detailed genetic contexts.